The written and the world in early medieval Iberia - Barrett, G (2015)
The written was the world of early medieval Iberia. Literacy was limited, but textuality was extensive, in the authority conferred on text and the arrangements made to use it. Roman inheritance is manifest, in documentary and legal culture, engendering literate expectations which define the period; continuity across conquest by Visigoths and Arabs, and the weakness of states in the north of the Peninsula, must lay to rest the traditional coupling of literacy with politics which underlies the paradigm of the Middle Ages. Between the eighth and eleventh centuries, as estates expanded to surmount locality and enter communities which had made do with memory, engagement with documentation was incentivized for the laity. Organization to do so followed, at one remove: the person of the scribe, who wrote the charter and recorded all those involved in and present at it, before recycling the text back into the community by public reading. The scribe mediated the text, and as his occupation consolidated he became more fully a literate interpreter. The charter, once created, had an active afterlife of dynamic circulation, enabled by multiple and accessible archives, particularly in the hands of the clergy. Written evidence was the surest defence in case of dispute; charters were self-promoting in their mutual citation as well as practical efficacy. But they also diffused legal knowledge: as each rhetorical, pragmatic, silent, and legislative reference to written law was read aloud by the scribe, how to capitalize on its provisions became better known, so kings and counts seized the potential. For the clergy, the Bible, canon law, and monastic rules were the texts which bestowed identity, but as they interacted with the laity, they set the charter in the history of salvation, and modelled textuality to society, as their monasteries became the microcosms of its written framework.